Effects of delayed cord clamping on the clinical outcomes of infants of diabetic mothers - Dickson, Johanny; Gordon, Ronique; Lew, Lily; Cohen, Lourdes (International Journal of Contemporary Pediatrics, 2025)
Background: Objectives was to evaluate the effect of delayed cord clamping (DCC) on the clinical outcomes in infants of diabetic mothers (IDM). Methods: Retrospective chart review of term singleton IDM at a single community hospital in New York from June 1, 2022, to April 30, 2023. Data was extracted from maternal and neonatal electronic health records (EHR). Infants who had DCC were compared to those who did not have DCC. Data were analyzed using statistical package for social sciences (SPSS), percentages, student t test, chi square, and Fisher’s exact test, p<0.05 was considered significant. Results: Out of a total of 584 IDM, 397 neonates met the inclusion criteria. The DCC group included 211 (53%) and the no-DCC group 186 (46%) neonates. Maternal and infant baseline characteristics were similar. There were no significant differences between the groups regarding neonatal intensive care unit (NICU) admission hypoglycemia, respiratory distress, mean hematocrit levels, hyperbilirubinemia, and length of stay (LOS). Conclusions: DCC did not alter the neonatal outcomes in IDM.